Didáctica de la programación lineal con el método gráfico - León Parada, Fernando (Revista Científica, 2006)
The graphic method is a good tool for solving mathematical models whose are related to optimization problems; with this method a typical problem of linear programming can be solved by simply evaluating the values of the objective function at the boundary vertices of the feasible region, this results of applying a special mathematical theorem for linear functions.